(untitled) (Palíndromo, 2022)
The objective of this article is to characterize, in an introductory way, certain ritual artistic practices performed in Candomblé, from the nation of Ketu, such as the songs of the African deities, named Orixás, the choreographed dances, the atabaques beats and the customs, in a way that to understand them from the ìtàn, the mythologies related to these deities. It is also intended to verify the relationship of these artistic practices with the fruition of axé, that is, the atabaques beats, the songs and the dances prepare the bodies of the Ẹlẹ́gùn for the personification of the Orixás, so that when one obtains the accuracy in the execution of the songs, the dances, the composition of the clothes, the Orixás insignia and even in the saints’ daughters conduct during the rite, there is the fruition of axé, capable of transforming and achieving, and this creative process then ensures the unfolding of existence itself. To support this analysis, we consider the dialogues established, through interviews, with Ìyálòrìsà Márcia Ty Ọ̀ṣun and with Bàbálòrìsà Fábio ty Ọ̀ṣọ́ọ̀si, priests in the Ilê Erô Opará Ofá Odé Asé Jaynã. It also used bibliographic research, in particular, directed to the writings of Ìyálòrìsà Gisselle Cossard-Binon, José Beniste, Muniz Sodré, Pierre Verger, Vilém Flusser, among others. It is worth noting that such practices and knowledge represent, in Brazil, aspects of yoruba culture and history, originally from Benin, Togo and Nigeria, Sierra Leone, among other countries.